Cover Feature: Double‐Network Ionogel Electrolyte with Superior Mechanical Performance and High Safety for Flexible Lithium‐Ion Batteries (ChemElectroChem 14/2022). Issue 14 (22nd June 2022) - Li, Zhen; Chu, Lin; Li, Suli; Chen, Weiping; Li, Ziyong; Guo, Panlong; Hu, Renzong
Abstract : The Cover Feature shows a double‐network ionogel electrolyte (DNIE) through the preparation of interpenetrating polymer networks. This DNIE exhibits good mechanical properties, excellent flexibility, nonflammability, high ionic conductivity, electrochemical stability (>4.8 V), and the ability to suppress Li dendrite formation. More information can be found in the Research Article by Z. Li et al .